UPAYA PENCEGAHAN STUNTING MELALUI MEDIA ULAR TANGGA PADA ANAK USIA SEKOLAH: UPAYA PENCEGAHAN STUNTING MELALUI MEDIA ULAR TANGGA PADA ANAK USIA SEKOLAH - Qasim, Muhammad Qasim; Juwita, Helmi; Sartika MS, Dewi (JCS, 2024)
Abstract One of the efforts to prevent stunting is to provide stunting prevention education through snakes and ladders media. This community service aims to provide education on stunting prevention to school age children according to their role using stunting snakes and ladders media. This community service was carried out in Kampung Savana, Makassar City using snakes and ladders stunting media for school age children. Before education is carried out, a pre-test is carried out to determine knowledge of stunting prevention in children using a questionnaire and a post-test is carried out after stunting prevention education. The results of the service showed changes in knowledge in school-age children after education on stunting prevention was carried out through snakes and ladders media.